Border of Ethics and Law: A Critique of the Theory of “Denying the Entry of Law into the Scope of the Veil” (Comparative Study of Islam, Iran, and Europe) - Reza Zahravi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The decriminalization approach can be corrected in some individual or social dimensions. The dimensions of the veil are not limited to the individual scope and have many social effects, but the neglect of social effects and neglect of other dimensions are against the principles of Islamic law and can be criticized. The realm of law is not limited to the social sphere, and the individual and divine dimensions are not outside the sphere of law, and the entry of law into this realm is rationally defensible and is based on the correct drawing of the boundary between ethics and law; Accordingly, in this article, on the one hand,   by presenting logical arguments for the entry of law into all necessary human relations, under the correct draw of moral and legal boundaries, criticizes arguments against entering the law in other cases to individual scope. On the other hand, as a violation argument, an attempt has been made to prove the entry of law into the subject of the veil by referring to and analyzing various domestic and foreign laws due to the social dimensions of the veil.